Analyses of Large Deflections for Logarithmical Bimodulus Cantilever Beams - Eren, Ibrahim (SAGE PUBLICATIONS LTD, 2009)
In this study, large deflections of non-linear bimodulus cantilever beams that have logarithmical stress-strain relationship have been analyzed when the beam was subjected to a moment at the free end. Effect of stress-strain relationship differences on the vertical and horizontal deflections have been determined for tension and compression. The numerical results, which indicate the affect on the engineering strain and true strain on deflections by means of divergence or convergence, were given in tables.
Keywords: non-linear bimodulus material; large deflections; logarithmical stress-strain; cantilever beams; end moment; NON-LINEAR MATERIALS; Materials Science; Polymer Science